2018
DOI: 10.1186/s12879-018-2993-0
|View full text |Cite
|
Sign up to set email alerts
|

Development of tissue inflammation accompanied by NLRP3 inflammasome activation in rabbits infected with Treponema pallidum strain Nichols

Abstract: BackgroundThe inflammasome responses in Treponema pallidum infection have been poorly understood to date. This study aimed to investigate the expression of the nucleotide-binding leucine-rich receptor protein 3 (NLRP3) inflammasome in the development of tissue inflammation in rabbits infected with T. pallidum.MethodsForty-five rabbits were randomly assigned to a blank group or an infection group, and the latter was divided into no benzathine penicillin G (BPG) and BPG treatment subgroups. Rabbits in the infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 22 publications
2
29
0
Order By: Relevance
“…10 Treponema pallidum-induced activation of the NLRP3 inflammasome led to elevated levels of pro-inflammatory cytokines and was closely linked to the development and progression of syphilitic inflammation. 2 Prior studies have noted that activation of the NLRP3 inflammasome modulates autophagy to enhance intracellular clearance of mycobacteria. 21 The results of our study also showed that transfected siRNA targeting NLRP3 reduced the level of autophagy and attenuated macrophage phagocytosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 Treponema pallidum-induced activation of the NLRP3 inflammasome led to elevated levels of pro-inflammatory cytokines and was closely linked to the development and progression of syphilitic inflammation. 2 Prior studies have noted that activation of the NLRP3 inflammasome modulates autophagy to enhance intracellular clearance of mycobacteria. 21 The results of our study also showed that transfected siRNA targeting NLRP3 reduced the level of autophagy and attenuated macrophage phagocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies found that T. pallidum induced the NLRP3 inflammasome in a dose-and time-dependent manner. 2,10 Since autophagy has been identified as an efficient means for host cells to eradicate intracellular pathogens, we next evaluated the role of the NLRP3 inflammasome in modulating the autophagic response in T. pallidum-infected macrophages. Real-time PCR showed that the relative mRNA levels of NLRP3, caspase-1, Beclin-1 and LC3B in the si-NLRP3 group were 43.04%, 37.63%, 49.86% and 43.02%, respectively, ( Fig.…”
Section: Effect Of Nlrp3 On Autophagy and T Pallidum Phagocytosis Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Syphilis is an infectious, sexually transmitted disease resulting from infection by Treponema pallidum [ 1 , 2 ]. Develop lesions in compromised tissues of infected patients are a direct manifestation of the inflammatory processes triggered by T. pallidum [ 2 4 ]. T.pallidum ’ pathogen-associated molecular patterns are recognized by the host immune system through pattern recognition receptors expressed by macrophages or dendritic cells, including intracellular receptors and membrane-bound [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Develop lesions in compromised tissues of infected patients are a direct manifestation of the inflammatory processes triggered by T. pallidum [ 2 4 ]. T.pallidum ’ pathogen-associated molecular patterns are recognized by the host immune system through pattern recognition receptors expressed by macrophages or dendritic cells, including intracellular receptors and membrane-bound [ 4 6 ]. This recognition of pathogen-associated molecular patterns activates various members of the nucleotide-binding leucine-rich receptor (NLR) family in the cytoplasm, which results in the assembly of an NLR-containing multiprotein complex that recruits and activates caspase-1 and thereby in the production of proinflammatory cytokines, including interleukin (IL)-1β, IL-18 and IL-33.…”
Section: Introductionmentioning
confidence: 99%